THE LOAN-TO-DEPOSIT RATIO AND ITS IMPACT ON BANK PROFITABILITY (World Economics and Finance Bulletin, 2025)
This article examines the concept of the Loan-to-Deposit Ratio (LDR) and its impact on bank profitability. LDR is analyzed as an important indicator reflecting how efficiently a bank utilizes its financial resources and its level of liquidity. The article discusses the method of calculating the ratio, the advantages and disadvantages of high and low LDR values, and the influence of economic conditions and regulatory requirements. It highlights that a high LDR can increase interest income but may pose liquidity risks, while a low LDR can ensure safety but limit income opportunities. The article emphasizes strategies for determining an optimal LDR for banks and the importance of risk management. Furthermore, it evaluates the LDR indicator in commercial banks of the Republic of Uzbekistan and its effect on the efficiency indicators of the national banking system.
Keywords: Loan-to-Deposit Ratio; Return on Assets; Return on Equity